Posyandu dalam era transformasi integrasi layanan primer dan intervensinya - Kusrini, Agatha Ratri Rini; Natalio, Rahmat; Sinaga, Evi Susanti (Indonesian Public Health-Observer Information Forum (IPHORR) Kerja sama dengan: Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2025)
Background: Lifecycle-based health services are a strategic approach to primary care transformation in Indonesia, positioning the Integrated Health Post (Posyandu) as a crucial community-based service. However, the implementation of Posyandu still faces various obstacles, such as a lack of trained cadres, suboptimal health education, and limited educational facilities and media, particularly in reaching target groups. Purpose: To evaluate the implementation of integrated Posyandu and to increase the capacity of cadres through outreach and the development of educational media. Method: This community service activity was conducted in Kebon Baru Village in January 2025. Eight participants participated. The first stage involved identifying Posyandus based on the lifecycle, encompassing a systems approach, evaluating input, process, and output aspects, and observing the service process directly at the Posyandu. The second stage involved providing education and developing educational media to enhance cadre knowledge and facilitate knowledge transformation. Results: Data obtained showed that the level of knowledge of cadres before the outreach activity was categorized as good (4%, 50%) and poor (4%, 50%). Meanwhile, the level of knowledge after being given extension activities was in the good category as many as 7 (87.5%) and in the less category as many as 1 (12.5%). Conclusion: Integrated health post (Posyandu) activities have implemented life cycle or integrated services, which, based on the identification results, are actively running and have been awarded the